Determann's field guide to data privacy law : international corporate compliance - Determann, Lothar (Elgar compliance guides, 2017)
Companies, lawyers, privacy officers and marketing and IT professionals are increasingly facing privacy issues. While information is freely available, it can be difficult to grasp a problem quickly, without getting lost in details and advocacy. This is where Determann's Field Guide to Data Privacy Law comes into its own - identifying key issues and providing concise practical guidance for an increasingly complex field shaped by rapid change in international laws, technology and society. This third revised edition includes significant changes to data privacy law since 2015 such as the challenges companies face as they move data to cloud solutions. With data privacy law enforcement at an all time high, readers will benefit from this introduction to key data privacy concepts and the useful practical guidance on starting, maintaining and auditing compliance programs.-